An analysis of the Implications of risk based audit on quality of financial reporting: case of Ministry of Agriculture, Mechanization and Irrigation Development - Muridzi, Judith (Midlands State University, 2015)
The research was on the analysis of the implications of risk based audit on quality of financial reporting on the Ministry of Agriculture, Mechanization and Irrigation Development. The objective of this study is to identify the impact of risk based audit on financial reporting and it articulated the relationship between audit risk-based audit and quality financial reporting. Literature from different scholars was discussed in this study. Audit practices and financial reporting practices which are used, at the Ministry of Agriculture, Mechanization and Irrigation Development. The weaknesses and strengths of accrual and cash basis accounting are also given. The research is quantitative in nature. The research was based on case study of Ministry of Agriculture, Mechanization and Irrigation Development. Likert scale questionnaires and structured interviews were used as research instruments. The analyses was made from the findings shows that audit risk and quality financial reporting have a positive relationship. This means that increase in risk-based audit will also result in increased quality financial reporting. The study also recommends full adoption of risk-based audit by the Ministry of Agriculture, Mechanization and Irrigation Development. Since, the practice of risk based audit has benefits that a substantial to true and fair presentation of financial information